Hierarchical phenomena in multicomponent liquids: simulation methods, analysis, chemistry. Issue 18 (10th March 2020) - Servis, Michael J.; Martinez-Baez, Ernesto; Clark, Aurora E.
Abstract : Complex, multicomponent, liquids benefit from a hierarchical understanding of solution speciation, collective organization and dynamics. Abstract : Complex, multicomponent, solutions have often been studied solely through the lens of specific applications of interest. Yet advances to both simulation methodologies (enhanced sampling, etc. ) and analysis techniques (network analysis algorithms and others), are creating a trove of data that reveal transcending characteristics across vast compositional phase space. This perspective discusses technical considerations of the reliable and accurate simulations of complex solutions, followed by the advances to analysis algorithms that elucidate coupling of different length and timescale behavior (hierarchical phenomena). The different manifestations of hierarchical phenomena are presented across an array of solution environments, emphasizing fundamental and ongoing science questions. With a more advanced molecular understanding in hand, a quintessential application (solvent extraction) is discussed, where significant opportunities exist to re-imagine the technical scope of an established technology.